Systematic Review of N-of-1 Studies in Rare Genetic Neurodevelopmental Disorders: The Power of 1. (16th March 2021) - Müller, Annelieke R.; Brands, Marion M.M.G.; van de Ven, Peter M.; Roes, Kit C.B.; Cornel, Martina C.; van Karnebeek, Clara D.M.; Wijburg, Frits A.; Daams, Joost G.; Boot, Erik; van Eeghen, Agnies M.
Abstract : Objective: To improve the use of N-of-1 studies in rare genetic neurodevelopmental disorders, we systematically reviewed the literature and formulated recommendations for future studies. Methods: The systematic review protocol was registered in the PROSPERO International Prospective Register of Systematic Reviews (CRD42020154720). EMBASE and MEDLINE were searched for relevant studies. Information was recorded on types of interventions, outcome measures, validity, strengths, and limitations using standard reporting guidelines and critical appraisal tools. Qualitative and descriptive analyses were performed. Results: Twelve studies met the N-of-1 inclusion criteria, including both single trials and series. Interventions were mainly directed to neuropsychiatric manifestations. Main strengths were the use of personalized and clinically relevant outcomes in most studies. Generalizability was compromised due to limited use of validated and generalizable outcome measures. Conclusion: N-of-1 studies are sporadically reported in rare genetic neurodevelopmental disorders. Properly executed N-of-1 studies may provide a powerful alternative to larger randomized controlled trials in rare disorders and a much needed bridge between practice and science. We provide recommendations for future N-of-1 studies in rare genetic neurodevelopmental disorders, ultimately optimizing evidence-based and personalized care.